Miejsce ojca wśród znaczących innych oczyma młodzieży w świetle badań CBOS - Gębka, Mikołaj (Człowiek i Społeczeństwo, 2024)
Significant others are the people who maintain close relationships with an individual and who influence the individual’s functioning. In case of youth this category typically includes their parents, siblings, partners (boyfriends or girlfriends) as well as peers. Significant others can also be defined as people who have particular bearing on the individual’s primary socialization. The latter is usually chiefly influenced by the parents. This article aims firstly to demonstrate the position of the father among significant others the view of young people, using the results of CBOS (Public Opinion Research Center) social opinion surveys. Secondly, the purpose of the article is to compare the educational roles which both parents enact as a young person’s partners in discussions on politics, school, future plans, personal issues and sex.